Metachromatic leukodystrophy: Biochemical characterization of two (p.307Glu→Lys, p.318Trp→Cys) arylsulfatase A mutations - Özkan, Adem (Intractable Rare Dis Res, 2016)
Metachromatic leukodystrophy (MLD) is a lysosomal storage disease caused by Arylsulfatase A (ASA) deficiency. The hallmark of the disease is central and peripheral neurodegeneration. More than 200 mutations have been identified in ARSA gene so far. Some of these mutations were characterized. The aim of this study is to reinforce genotype-phenotype correlation and to understand the effect of mutations on the enzyme by biochemical characterization. Two missense mutations (c.919G→A, p.307Glu→Lys and c.954G→T, p.318Trp→Cys in exon 5) were constructed on WT-ASA cDNA and were confirmed by DNA sequence analysis. Plasmid DNA carrying mutant or normal ASA cDNA was transferred to Chinese Hamster Ovary (CHO) cells through transient transfection. ASA protein was produced by CHO cells. Hexosaminidase beta-subunit gene was cotransfected into the CHO cells as a control gene of transfection efficiency. 48 hours after transfection, cells were collected and homogenized. ASA and hexosaminidase activities were measured in supernatant. ASA enzyme activity is decreased 100% according to the control by the effect of both mutations. The mutations are located in the higly conserved region of the protein. In this study, we showed that both mutations result in null ASA activity in CHO cells making the protein nonfunctional. We confirmed that p.307Glu→Lys and p.318Trp→Cys mutations cause late infantile form of MLD disease.